2020
DOI: 10.1021/acs.jpcc.0c08715
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Influence of Bilayer Structure on Energy Transfer and Molecular Photon Upconversion in Metal Ion Linked Multilayers

Abstract: Metal ion linked multilayers are a unique motif to spatially control and geometrically restrict molecules on a metal oxide surface, which is of interest in a number of promising applications. Here we use a bilayer composed of a metal oxide surface, an anthracene annihilator molecule, Zn(II) linking ion, and porphyrin sensitizers to probe the influence of the position of the metal ion binding site on energy transfer, photon upconversion, and photocurrent generation. Despite being energetically similar, varying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(50 citation statements)
references
References 88 publications
7
43
0
Order By: Relevance
“…But previous results have shown that metal ion coordination and bilayer formation has minimal impact of the intrinsic photophysical properties of the first layer chromophore. 47 In the early time slices we see a distinct peak at B600 nm that is consistent with the excited state absorption from 1 A* in solution (red spectrum in Fig. 6).…”
Section: Energy and Electron Transfer Dynamicssupporting
confidence: 74%
See 2 more Smart Citations
“…But previous results have shown that metal ion coordination and bilayer formation has minimal impact of the intrinsic photophysical properties of the first layer chromophore. 47 In the early time slices we see a distinct peak at B600 nm that is consistent with the excited state absorption from 1 A* in solution (red spectrum in Fig. 6).…”
Section: Energy and Electron Transfer Dynamicssupporting
confidence: 74%
“…But previous results have shown that metal ion coordination and bilayer formation has minimal impact of the intrinsic photophysical properties of the first layer chromophore. 47…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first report of utilizing TTA-UC for sunlight to electrical conversion in 2012, notable advancements have been made in harnessing the photocurrent contribution from UC ( J UC ), with the progress to date summarized in Figure . This graph includes device relevance and device impact thresholds, which are roughly the minimum J UC to overcome PCE measurement uncertainties (0.1 mA/cm 2 ) and a >1 percentage point increase in PCE (1.0 mA/cm 2 ), respectively. , …”
mentioning
confidence: 99%
“…To date, TTA-UC has been incorporated into both dye-sensitized solar cells (DSSCs) , and organic photovoltaic (OPV) device architectures, as well as a proof-of-concept hybrid film . The DSSC motif is most common with heterogeneous, codeposited, and metal-ion-linked architectures shown in Figure .…”
mentioning
confidence: 99%